STUDENTS’ PERCEPTIONS OF VIRAL TIKTOK ENGLISH SONGS AS EFL VOCABULARY LEARNING PLATFORM - Azadat Wiqoyatin Nur; Zulfa Sakhiyya (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2026)
This study aims to explore EFL students’ perceptions of viral TikTok English songs as a tool for vocabulary learning. In today’s digital era, social media platforms such as TikTok have become a part of students’ daily lives and offer new possibilities for integrating entertainment into education. Viral English songs on TikTok are often catchy and memorable, making them potential media for improving students’ vocabulary acquisition in an enjoyable way. This research used a quantitative descriptive survey involving 52 English Education students at Universitas Negeri Semarang, selected through a pre-survey screening to ensure they were active TikTok users familiar with viral English songs. A 15-item Likert-scale questionnaire measured three aspects which are students’ engagement, vocabulary acquisition, and perceptions of TikTok as a learning tool. The data were analyzed through reverse coding of negative items, reliability testing using Cronbach’s Alpha, and descriptive statistics. The results show that students were highly engaged with TikTok English songs and reported meaningful vocabulary gains supported by repeated and contextual audiovisual exposure. Students also showed positive attitudes toward TikTok, finding it enjoyable and useful for learning, which aligns with theories of comprehensible input, multimedia learning, and the Technology Acceptance Model. Overall, the study suggests that viral TikTok English songs can function as an effective supplementary tool for increasing engagement and supporting vocabulary learning in EFL settings.